4. CLINICAL, EEG CHARATERISTICS AND TREATMENT OF EPILEPSY IN CHILDREN AT CAN THO CHILDREN'S HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Background: Epilepsy is a chronic disease that affects the brain. New-onset epilepsy cases are common in young children, especially in the first year of life. Epilepsy diagnosis based on electroencephalogram combined with clinical examination helps detect the disease early for effective treatment.Objectives: (1) Describe the clinical and EEG characteristics of epilepsy in children at Can Tho Children's Hospital in 2023 – 2024; (2) Evaluate the results of treatment of epilepsy in children children at Can Tho Children's Hospital in 2023 - 2024.Method: Retrospective description of over 100 pediatric patients diagnosed with epilepsy treated at Can Tho Children's Hospital from March 2023 to March 2024.Results: The majority of children with pediatric epilepsy onset is between the ages of 1-10 years old (76%), with the highest rate being in the 1-5 year old group (42%). 2% of children with epilepsy have mental retardation. Classification of generalized seizures accounts for 57% and partial seizures accounts for 43%. In generalized seizures, tonic-clonic seizures are the most common type of seizure (42.1%), simple partial seizures are the most common type (60.5%). 60% of pediatric epilepsy patients had normal EEG results, 23% of pediatric patients recorded images localized to one hemisphere and 17% had uniformly diffuse images in both hemispheres. Valproic acid (Depakin) was the most commonly used treatment (76%). Treatment results showed that 100% of children had symptoms improved or reduced after treatment. The average treatment duration of treatment is 7.99 ± 2.87 days, (3 days - 15 days).Conclusion: Clinical characteristics of pediatric epilepsy patients show that in generalized seizures, tonic-clonic seizures are the most common type of seizure, and in partial seizures, simple partial seizures are the most common type, many children have Electroencephalogram normal. All treated patients experienced improvement and reduced symptoms after 8 day.
Keywords: Epilepsy, children, treatment.